Penerapan Metode Brainwriting terhadap Gambar Berantai pada Keterampilan Menulis Puisi Kelas VIII-A SMP Laboratorium UM - Adiningsih, Aisyah; Karkono, Karkono (Journal of Language Literature and Arts, 2024)
This study explores the implementation of brainwriting to chain images as a method to enhance poetry writing skills. Employing a descriptive qualitative approach, the research applies the STAR method (Situation, Task, Action, and Result) to analyze the effectiveness of this approach. Data collection methods include observation, questionnaire administration, testing, and document analysis. The study focuses on students in class VIII-A of UM Laboratory Middle School, comprising 32 students, with 14 male and 18 female participants. By utilizing the brainwriting technique to generate and connect ideas for image chaining, students' engagement and motivation in learning are expected to increase. The subsequent discussion sessions following brainwriting activities facilitate the exchange of perspectives and emotions among students regarding the chained images, fostering empathy and deeper understanding. The collaborative nature of the padlet platform enhances communication and interaction among students, creating a conducive environment for exploring and expressing ideas. Through this process, students not only improve their poetry writing skills but also develop their ability to interpret and convey emotions through visual imagery. Overall, the findings suggest that incorporating brainwriting into poetry writing sessions can be an effective strategy to stimulate creativity and enhance students' learning experience in poetry composition.